2019
DOI: 10.5433/1679-0359.2019v40n6supl2p3181
|View full text |Cite
|
Sign up to set email alerts
|

Use of emulsifier and lipase in feeds for broiler chickens

Abstract: The objective of this study was to evaluate the effect of exogenous emulsifier and lipase in diets on performance, digestibility, and organ biometry of broiler chickens. A completely randomised design with seven treatments and seven replications was adopted. The treatments were as follows: T1 (positive control; PC): 3000, 3100, 3200, and 3250 Kcal of metabolisable energy (ME) kg-1 of diet for phases 1 to 10, 11 to 21, 22 to 31, and 32 to 37 days, respectively; T2: PC with reduction in ME of 30 Kcal kg-1 of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…Fats and oils are the most essential energy sources in broilers' diets as a worthy way for gathering the high energy demands for the highest growth rates of broiler chickens [1,2]. In addition, the evident merits of high-caloric-density lipids result in an excellent caloric impact [3,4]. The failure of the broilers to gain lipids is assigned to bad emulsification rather than the shortage in lipase secretion, which led to great interest in the possibility of using exogenous emulsifiers to improve the utilization of lipids in broiler chickens [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fats and oils are the most essential energy sources in broilers' diets as a worthy way for gathering the high energy demands for the highest growth rates of broiler chickens [1,2]. In addition, the evident merits of high-caloric-density lipids result in an excellent caloric impact [3,4]. The failure of the broilers to gain lipids is assigned to bad emulsification rather than the shortage in lipase secretion, which led to great interest in the possibility of using exogenous emulsifiers to improve the utilization of lipids in broiler chickens [5].…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors that limits using high levels of fat in broiler diets is the indigestion of fat, because bile secretion in broilers is not efficient in the first days of age [10]. In this time, using exogenous emulsifiers in the high-fat diet enhances fat utilization and digestive metabolism [3,5]. Moreover, San Tan et al [11] recommended that supplementation of emulsifiers in the early stages of age improved digestion and absorption of the fats and enhanced growth performance in broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effects of the fat type in broiler diets, previous studies indicated that the source of fat does not influence the deposition of other nutrients in the animal carcass (Kanakri et al, 2017(Kanakri et al, , 2018Maniila et al, 1999) or the dry matter digestibility (Oliveira et al, 2019), but influence the composition of fatty acids (Gaiotto et al, 2000). Studies conducted by (Rodriguez-Sanchez et al, 2019) reported that the broiler's age influences the digestibility with an absorption restriction in broilers at the starter phase, regardless of the tested fat source.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhao et al (12) , the inclusion of an emulsifier reduces abdominal fat yield, but this result was not observed in the present study. In fact, Oliveira et al (13) found no influence on the use of emulsifiers on fat deposition in the abdominal region of birds.…”
Section: Carcass Yieldmentioning
confidence: 95%